A Case of Primary Breast Diffuse Large B-Cell Lymphoma Treated with Chemotherapy Followed by Elective Field Radiation Therapy: A Brief Treatment Pattern Review from a Radiation Oncologist's Point of View. (13th July 2015) - Lee, Kyu Chan; Lee, Seung Heon; Sung, KiHoon; Ahn, So Hyun; Choi, Jinho; Lee, Seok Ho; Lee, Jae Hoon; Hong, Junshik; Park, Sang Hui
Abstract : We here report a case of primary breast lymphoma (PBL). A 44-year-old woman presented with a painless mass in the right breast. Fine needle aspiration cytology and excisional biopsy were performed. Excisional biopsy revealed low grade lymphoma, which was subsequently confirmed with histopathology and diagnosed as diffuse large B-cell lymphoma (DLBCL). A chest computed tomography scan revealed a 3.5 cm sized breast mass with skin thickening and a small sized lymphadenopathy in the ipsilateral axilla. Radiation therapy including the right whole breast and ipsilateral axilla and supraclavicular lymph node was performed after the patient received four courses of R-CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone plus rituximab) chemotherapy. At the follow-up period of 42 months, the patient is surviving with no evidence of disease. No morbidities occurred in this patient during the follow-up period. We also briefly review the current practice pattern in PBL patients with DLBCL.